Pengaruh Persepsi Konsumen Pasca Kasus Surat Komplain Eiger Terhadap Keputusan Pembelian - Anisa Febriani; Azaria Ainun Halila; Dyva Claretta; Ahimsa Adi; Khansa Maritza (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2022)
PT Eigerindo Multi Produk Industri is a company known in manufacturing and retailing various adventure attributes including sports. The background of this research was when Eiger Adventure made a complaint and issued a subpoena through the official Instagram account @eigeradventure against @duniadian who made a review of eyewear products by a customer on his personal YouTube channel. The purpose of the research was to find out the buying interest of the public and Eiger customers after a review complaint that went viral on the social media platform, namely Twitter. Interviews were conducted with 8 active student informants who use the brand from Eiger. The results of the interview data between Eiger's customer buying interest after the complaint case and the subpoena issued by Eiger are in accordance with several points, namely 1.) Consumer Behavior 2.) Consumer Decision Making 3.) Consumer Trust 4.) Purchase intention.